Human resource management and its impact on employee performance in MSMEs—SLR - Hasibuan, Rahman; Arnesih,; Anggraini, Dini; Yona, Mira; Hisyam, Magneta; Lubis, Ulfi Sartika (Frontiers in Sustainability, 2026)
Small and Medium Enterprises (UMKM) play a pivotal role in Indonesia’s economy, contributing significantly to the Gross Domestic Product (GDP) and providing employment opportunities. However, the productivity and sustainability of UMKM are highly influenced by the quality of Human Resources (HR) management. This research systematically reviews existing literature on Human Resource Management (HRM) practices and their impact on employee performance within UMKM, focusing on the period between 2020 and 2025. The study aims to explore how HRM practices, such as recruitment, training, employee recognition, and the adoption of innovative management strategies affect employee performance and, consequently, the overall performance of UMKM. The research questions address the effects of sustainable HRM practices, the responsiveness of HRM to industrial changes, and the role of innovation-oriented HRM in enhancing employee performance. Using a systematic literature review (SLR) methodology, the study aggregates findings from various articles indexed in Scopus, MDPI, and other reputable databases. The findings indicate that effective HRM practices, including structured recruitment, continuous training, employee engagement, and the integration of technology, significantly enhance employee motivation, satisfaction, and productivity. Moreover, sustainable HRM approaches that focus on employee welfare and long-term development are found to reduce turnover rates and improve organizational commitment. The study concludes that UMKM can increase their competitiveness and ensure long-term sustainability by adopting HRM practices that are adaptive to technological advancements and industry changes, particularly in the context of the fourth industrial revolution.